2022
DOI: 10.1007/s13311-022-01294-9
|View full text |Cite
|
Sign up to set email alerts
|

Treatment-Specific Network Modulation of MRI-Guided Focused Ultrasound Thalamotomy in Essential Tremor

Abstract: MRI-guided focused ultrasound (MRgFUS) thalamotomy is a novel, effective, and non-invasive treatment for essential tremor (ET). However, the network mediating MRgFUS in treating ET is not precisely known. This study aimed to identify the disease-specific network associated with the therapeutic effects of MRgFUS thalamotomy on ET and investigate its regional characteristics and genetic signatures to gain insights into the neurobiological mechanism of ET and MRgFUS thalamotomy. Twenty-four ET patients treated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…27 However, few studies have used this approach to explore the changes in the WM network in patients treated to MRgFUS. 6,8 This study found a great improvement in the strength of rich-club connection after MRgFUS thalamotomy compared to pre-operation, while the connections between hub nodes and peripheral nodes vs. peripheral nodes and peripheral nodes were not statistically significant. It has been speculated that whether these changes in WM network induced by MRgFUS are driven by the strength of rich-club connections in ET patients, which is worth further exploration.…”
Section: Discussionmentioning
confidence: 70%
See 4 more Smart Citations
“…27 However, few studies have used this approach to explore the changes in the WM network in patients treated to MRgFUS. 6,8 This study found a great improvement in the strength of rich-club connection after MRgFUS thalamotomy compared to pre-operation, while the connections between hub nodes and peripheral nodes vs. peripheral nodes and peripheral nodes were not statistically significant. It has been speculated that whether these changes in WM network induced by MRgFUS are driven by the strength of rich-club connections in ET patients, which is worth further exploration.…”
Section: Discussionmentioning
confidence: 70%
“…38 A recent study has proposed that the therapeutic effects of MRgFUS thalamotomy on ET are associated with modulating a distinct ET-related network, including the sensorimotor and posterior cingulate cortex, which may be driven by mitochondria-relevant neurobiological mechanisms. 8 Another structural network study also supported this point that there was a U-shaped subnetwork sensitive to MRgFUS thalamotomy in patients with tremor-dominant PD. 6 Additionally, from the point of the network level, no significant changes within the ablated lesion was detected via modular analysis; however, a significant difference in left thalamus was reported via voxel-based analysis, also accompanied by changes in the motor area.…”
Section: Discussionmentioning
confidence: 80%
See 3 more Smart Citations